Outcome in patients who require renal support after surgery for ruptured abdominal aortic aneurysm. - Gordon, A; Pryn, S; Collin, J; Gray, D; Hands, L; Garrard, C (1994)
Over a 3-year period haemofiltration and dialysis was provided for 18 patients who developed renal failure after operation for ruptured abdominal aortic aneurysm (AAA). Four of the patients underwent operation elsewhere and were transferred when renal failure was diagnosed. The median duration of renal support in the 11 survivors was 24 days, while the seven patients who died received support for a median of 11 days. By 3 months after operation eight of the 11 survivors were independent of dialysis. Renal support was life saving in eight of 91 patients operated on in Oxford for ruptured AAA and reduced the 30-day operative mortality rate from a potential 47 per cent to an actual 38 per cent. Haemofiltration and haemodialysis for acute renal failure after surgery for ruptured aortic aneurysm is clinically justified and results in the long-term survival of most patients.